2013
DOI: 10.1593/tlo.13427
|View full text |Cite
|
Sign up to set email alerts
|

Age-Dependent Association between Protein Expression of the Embryonic Stem Cell Marker Cripto-1 and Survival of Glioblastoma Patients

Abstract: Exploring the re-emergence of embryonic signaling pathways may reveal important information for cancer biology. Nodal is a transforming growth factor-β (TGF-β)-related morphogen that plays a critical role during embryonic development. Nodal signaling is regulated by the Cripto-1 co-receptor and another TGF-β member, Lefty. Although these molecules are poorly detected in differentiated tissues, they have been found in different human cancers. Poor prognosis of glioblastomas justifies the search for novel signal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 78 publications
1
22
0
Order By: Relevance
“…Pilgaard et al (8) suggested that cripto-1 may be a prognostic biomarker for glioblastoma multiforme (GBM) with the potential of being a therapeutic target. Tysnes et al (9) observed that the majority of samples of patients with glioblastoma demonstrated significant levels of cripto-1, as it was detected by immunohistochemistry. Thus, numerous studies have demonstrated that cripto-1 may be a novel tumor-specific marker, and its value in early diagnosis of tumors, targeted treatment, drug resistance mechanisms and prognosis is of interest (3)(4)(5)(6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Pilgaard et al (8) suggested that cripto-1 may be a prognostic biomarker for glioblastoma multiforme (GBM) with the potential of being a therapeutic target. Tysnes et al (9) observed that the majority of samples of patients with glioblastoma demonstrated significant levels of cripto-1, as it was detected by immunohistochemistry. Thus, numerous studies have demonstrated that cripto-1 may be a novel tumor-specific marker, and its value in early diagnosis of tumors, targeted treatment, drug resistance mechanisms and prognosis is of interest (3)(4)(5)(6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 96%
“…An in-vivo study demonstrated that the growth of human nasopharyngeal carcinoma CNE-2 cells was significantly inhibited in cripto-1 knockout mice compared with the control group (7). Previous studies have demonstrated elevated cripto-1 expression in gliomas (8,9). Pilgaard et al (8) suggested that cripto-1 may be a prognostic biomarker for glioblastoma multiforme (GBM) with the potential of being a therapeutic target.…”
Section: Introductionmentioning
confidence: 99%
“…10 In another work, it was observed that higher Cripto-1 scores were linked with reduced survival in younger GBM patient. 9 Cripto-1 is enriched in cancer cell subpopulations showing stem like cell characteristics. For example, in embryonal carcinoma (EC), Cripto-1 exists in two distinct subpopulations (low and high).…”
mentioning
confidence: 99%
“…Over the past years, a substantial number of studies on many solid tumors including glioblastoma (Tysnes et al, 2013), breast cancer (Al-Hajj et al, 2003), prostate cancer (Collins et al, 2005), pancreatic cancer (Hermann et al, 2007), colorectal cancer and OSCC However, most of these stem cell markers including CD133, CD44,...etc. used in the above studies were empirical and derived from normal stem cells which are known to be largely tissue specific which inturn had raised an important question regarding the specificity and reliability of such CSC markers (Baillie et al, 2017 andLiu et al, 2017).…”
Section: Issn: 2320-5407mentioning
confidence: 99%